2021
DOI: 10.1515/npf-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Final Lines of Defense: Explaining Policy Advocacy by Immigrant-Serving Organizations

Abstract: Nonprofit scholars have developed a rich literature on nonprofit advocacy. While the literature is rich, however, gaps remain in our collective knowledge, especially regarding specific sectors of nonprofit human service organizations. Here, we apply existing theory on advocacy by human service organizations to an important subset of the nonprofit community, that being immigrant-serving organizations (ISOs). Most prior research on nonprofit advocacy has not focused on politically polarized issues, such as conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The highly complicated-and many would argue intentionally confusing-U.S. immigration system has made the need for immigration legal aid more pressing than ever (de Leon & Roach, 2013). Indeed, in a recent study, the authors of this piece found strong evidence that ISOs providing pro bono legal aid are effective at reducing local ICE removals through the agency's S-Comm program (Calderon et al, 2021).…”
Section: Isos As Advocatesmentioning
confidence: 98%
See 1 more Smart Citation
“…The highly complicated-and many would argue intentionally confusing-U.S. immigration system has made the need for immigration legal aid more pressing than ever (de Leon & Roach, 2013). Indeed, in a recent study, the authors of this piece found strong evidence that ISOs providing pro bono legal aid are effective at reducing local ICE removals through the agency's S-Comm program (Calderon et al, 2021).…”
Section: Isos As Advocatesmentioning
confidence: 98%
“…Policymakers to whom groups advocated varied greatly, from 69.2% saying they petitioned their state legislature to only 49.5% who reported advocating to the governor's office (Calderon et al, 2021).…”
Section: Isos As Advocatesmentioning
confidence: 99%
“…As a result, foreign-born individuals express stronger support for sanctuary city policies which can result in more supportive local policies (Casellas and Wallace 2020). Institutions such as labor organizations and local nonprofits can mobilize immigrant electoral activity even absent citizenship and the ability to vote (Varsanyi 2005; Calderon, Chand, and Hawes 2021) and anti-immigrant local policies can also stimulate political actions on the parts of immigrants and their allies (Benjamin-Alvarado, DeSipio, and Montoya 2009; Zepeda-Millán 2016). The contact hypothesis would also suggest that communities with greater diversity offer more opportunities for interactions among groups, leading to reduced stereotypes and potentially more support for immigrants (Connolly 2000).…”
Section: Theories Related To Attitudes About Immigrants Andnd Local I...mentioning
confidence: 99%
“…It occurs mainly in social work studies (Mosley 2010;MacIndoe and Whalen 2013;De Corte et al 2021). In recent years, specifically with the involvement of NGOs assisting immigrants in PA, the topic has occurred in several researches (Ambrosini 2013;Chin 2018;Follis 2019;Trei 2021;Calderon et al 2021); however, none of them delved very deeply into the question of legitimacy and accountability associated with this activity. Ambrosini (2013) explored the motivations, strategies, coalitions, and outcomes of the activities of two specific Italian NGOs.…”
Section: Ngos' Policy Advocacy In Research Studiesmentioning
confidence: 99%
“…Trei (2021) attempted to explain the involvement of Estonian NGOs in asylum policy decision making on the national level. Calderon et al (2021) addressed the general questions of engagement of American immigrants assisting organizations in policy advocacy (mainly if they engage, when yes, and when no). Thus, the presented study complements the understanding of NGOs involvement in policy advocacy.…”
Section: Ngos' Policy Advocacy In Research Studiesmentioning
confidence: 99%